Pelatihan Pembuatan Minumanan Moctail Dengan Bahan Dasar Komucha - Tito Pratama; Dewi Aurora Mikasari; Siska Amelia Maldin; Rezki Alhamdi (JURNAL KEKER WISATA, 2023)
Popular drinks such as coffee, tea, Boba drinks, and several other trending drinks are being loved in Indonesia. Cafes with attractive packaging selling various types of drinks can be easily found in big cities. One drink that is a favorite of many people is the kombucha mocktail. A kombucha mocktail is a drink made from kombucha, which is a fermented drink made from fermented sweet tea using mushroom cultivation. In Indonesia, kombucha mocktail drinks are increasingly popular with many variations of flavors and attractive packaging. This drink is not only refreshing, but also contains probiotics and enzymes that are beneficial for digestion. SMA is the last level of education before students continue on to college or enter the world of work. One of the well-known high schools in Batam City is SMAK Yos Sudarso which has quite a large number of students. The Batam Tourism Polytechnic has the opportunity to provide education and training to students there regarding kombucha mocktail drinks. They will be given knowledge about this drink, and then trained in making variations of kombucha mocktail drinks with an attractive appearance.